Factors determining window display conveying merchandise's Positioning and style: a case of shopping mall clothing display targeting undergraduate students - Kanokwan Somoon; Nopadon Sahachaisaeree (My University, 2010)
Window displays, as a part of selling strategies, not only convey the type and positioning of mechanize, but also the promotional strategies and corporate images. The study uses window displays for clothing to examine patterns, selling strategies, merchandize types, and target groups. It investigates the effects of design elements on the customers' perceptual responding to configurations. The theoretical framework bases on marketing concepts, visual perception principles, Gestalt psychology, and design's principle and elements. Sixty undergraduates, ages 18-23, participated as research subjects. Results derive a design guideline for window displays towards the designated type of intended perception for the particular group.
Keywords: Color perception and design